Organization and promoter analysis of the mouse dishevelled-1 gene. - Lijam, N; Sussman, D J

(untitled) (Genome Research, 1995)
We have characterized the genomic organization of a mouse homolog (Dvl-1) of Drosophila dishevelled, a segment polarity gene required for wingless signal transduction. The Dvl-1 gene is organized into 15 exons ranging in size from 68 to 1315 bp spanning a region of 12,409 bp, with the largest and smallest intron being 5545 and 71 bp, respectively. Sequence analysis of the 5'-flanking region of the gene revealed a high GC content, six CCGCCC Sp-1-binding motifs, CREB, LBP-1 (leader-binding protein 1), and TGGCA-binding consensus sites. However, neither TATA or CAAT boxes are present, a characteristic shared by other GC-rich promoters. The 5'-flanking region has strong promoter activity when placed upstream of the luciferase gene. Promoter-luciferase constructs have demonstrated that the promoter is functional in transfection assays and that its activity is orientation dependent. Promoter deletions were used to define the 5' and 3' boundaries for promoter activity and revealed the presence of both positive and negative regulatory elements. Multiple transcription initiation sites were mapped by primer extension analysis and confirmed by reporter gene assay.